The Genealogy of the 20th Century South Slavonic Novel: Zofka Kveder and Julka Chlapec-Djordjević (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper investigates different narrative strategies of two epistolary novels: Hanka (1915, 1917) by the Slovene-Croatian writer Zofka Kveder, (1878-1926), who lived before the First World War in Prague, and Jedno dopisivanje. Fragmenti romana (A Correspondence. Fragments of the Novel, 1932) by Julka Chlapec-Djordjević, (1882-1969), the Serbian author and feminist and ex-“monarchical” author, who was also in Prague after the First World War. Both women were feminists and writers who belonged to the Central European literary society. In addition, both of them were mediators between different cultures. Influenced by Zofka Kveder, Chlapec-Djordjević wrote her novel in a dialog with Kveder´s Hanka.
Keywords: Zofka Kveder; Julka Chlapec-Djordjević; Slavonic women writers in Prague; literature in Prague